2003
DOI: 10.1016/s0954-6111(03)00120-3
|View full text |Cite
|
Sign up to set email alerts
|

Pathological findings of bronchiectases caused by Mycobacterium avium intracellulare complex

Abstract: It has been argued whether bronchiectasis is truly caused by MAC infection or just a predisposed condition in which MAC colonizes. Our present study was designed to evaluate the pathological findings of bronchiectases caused by Mycobacterium avium intracellulare complex (MAC) lung infection and to demonstrate MAC in the lesion of bronchiectases. A retrospective study was performed in nine cases with positive cultures for MAC in whom lung resections were performed. A determination of whether or not MAC caused p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 21 publications
2
44
0
2
Order By: Relevance
“…One recent study suggested that granulomatous inflammation was the cause of bronchiectasis. In other presentations, such as that with cystic fibrosis (CF) or prior pulmonary TB, bronchiectasis clearly antedates MAC disease (123,132). For further discussion, see Risk Factors and Immunodeficiency Defects below.…”
Section: Treatment Of Nontuberculous Mycobacterial Infections Pulmonarymentioning
confidence: 99%
See 1 more Smart Citation
“…One recent study suggested that granulomatous inflammation was the cause of bronchiectasis. In other presentations, such as that with cystic fibrosis (CF) or prior pulmonary TB, bronchiectasis clearly antedates MAC disease (123,132). For further discussion, see Risk Factors and Immunodeficiency Defects below.…”
Section: Treatment Of Nontuberculous Mycobacterial Infections Pulmonarymentioning
confidence: 99%
“…The cell-mediated immune response produces an infiltration of lymphocytes, macrophages, and antigen-presenting cells. In turn, chronic inflammation leads to the destruction of the elastin layer in the bronchial walls (123).…”
Section: Underlying Bronchiectasismentioning
confidence: 99%
“…Although the presence of bronchiectasis predisposes colonization by opportunistic microorganisms such as NTM, it is also suggested that they play a role in the development of these bronchial disorders. Fujita et al retrospectively evaluated resected lung specimens from 9 patients infected with Mycobacterium avium complex [13]. In all the cases they identified destruction of bronchial cartilage and of the smooth muscle layer as well as bronchial mucosa ulcerations and the presence of airway granulomas.…”
Section: Postinfectiousmentioning
confidence: 99%
“…In all the cases they identified destruction of bronchial cartilage and of the smooth muscle layer as well as bronchial mucosa ulcerations and the presence of airway granulomas. Given these histopathological changes, the authors concluded that NTM infection could be a cause rather than a consequence of the appearance of bronchiectasis [13]. It has been suggested that certain host factors may increase the risk to develop pulmonary NTM infection [14].…”
Section: Postinfectiousmentioning
confidence: 99%
“…In bronchiectasis, destruction of bronchial cartilage and smooth muscle layer, bronchial ulceration and obstruction of airways by granulomas are common [54]. Otherwise, little is known on detailed airway abnormalities.…”
mentioning
confidence: 99%